Ferroptosis and cardiovascular disease: role of free radical-induced lipid peroxidation. (3rd April 2021) - Chen, Xin; Li, Xuan; Xu, Xiaodong; Li, Luxiao; Liang, Ningning; Zhang, Lili; Lv, Jingwen; Wu, Yun-Cheng; Yin, Huiyong
Abstract: Cardiovascular disease (CVD), including heart attack, stroke, heart failure, arrhythmia, and other congenital heart diseases remain the leading cause of morbidity and mortality worldwide. The leading cause of deaths in CVD is attributed to myocardial infarction due to the rupture of atherosclerotic plaque. Atherosclerosis refers a condition when restricted or even blockage of blood flow occurs due to the narrowing of blood vessels as a result of the buildup of plaques composed of oxidized lipids. It is well-established that free radical oxidation of polyunsaturated fatty acids (PUFAs) in lipoproteins or cell membranes, termed lipid peroxidation (LPO), plays a significant role in atherosclerosis. LPO products are involved in immune responses and cell deaths in this process, in which previous evidence supports the role of programmed cell death (apoptosis) and necrosis. Ferroptosis is a newly identified form of regulated cell death characterized by the iron-dependent accumulation of lipid hydroperoxides to lethal levels, which exhibits distinct features from apoptosis, necrosis and autophagy in morphology, biochemistry and genetics. Emerging evidence appears to demonstrate that ferroptosis is also involved in CVD. In this review, we summarize the recent progress on ferroptosis in CVD and atherosclerosis, highlighting the role of free radical LPO. The evidence underlying the ferroptosis and challenges in the field will also be critically discussed.